ASSOCIATION OF AGE WITH HEARING REHABILITATION AFTER COCHLEAR IMPLANT - Naeem, Fizza; Raza, Sayed Nusrat; Khan, Taimoor Ashraf; Aiman, Um e (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the hearing outcomes following unilateral cochlear implantation & speech therapy in patients with bilateral severe to profound sensorineural hearing loss.Study Design: Prospective observational study.Place and Duration of Study: Department of ENT, Head and Neck Surgery, Combined Military Hospital Rawalpindi, from Dec 2018 to Dec 2019.Methodology: We included 40 cases who underwent unilateral cochlear implantation at the Cochlear Implant Centre of Combined Military Hospital Rawalpindi and later on had at least 6 months of continuous speech rehabilitation (post-activation) at Speech Rehab Center of the same hospital. All patients had their cochlear implants activated 6 weeks after the surgery. Auditory rehabilitation was assessed continuously at each session by a single speech therapist and documented using the “5 stages of listening i.e. has a very good vocabulary, has a basic vocabulary, understands words, responds to sounds, doubtful response to sound.”Results: Out of 40 patients, 22 (55%) were male and 18 (45%) were females. Age at the time of cochlear implan-tation ranged from 2 to 8.4 years with a mean age of 4.5 ± 1.34 years. At 6 months 50% of children in age group 2-3 years had clinically and statistically significant response to speech rehabilitation post cochlear implant surgery. Conclusion: We concluded that a cochlear implant is a safe and highly effective treatment for bilateral severe to profound sensorineural deafness in pediatric age from 2 to 8 years while the best results documented in our study are for age 2 and 3 years at implantation.